The widely distributed, edible seaweeds in Peru, Chondracanthus chamissoi and Chondracanthus chamissoi f. glomeratus (Gigartinaceae, Rhodophyta), are morphologically diverse but not phylogenetically distinct - Arakaki, Natalia (2021)
Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica, Grant/Award Number: Convenio de Subvencion Nro. 017-2016-FONDECYT